Retaining Wall Designs for Soil Instability Control: A Case Study in Sapang Bato, Angeles City, Pampanga - Mamaradlo, Mailene Yesha; Cruz, Jolie Angela; Cruz, Kerby Christian; Layawon, Jennie Chris; Leron, Princess Karyll; Manese, Steven Charlie; Villagracia, Jordan; Manuntag, Ma. Luz; Zoleta, Juanita Carmelita (International Journal of Research in Interdisciplinary Studies, 2025)
This study focuses on the recurring issue of soil instability in Sapang Bato, Angeles City, Pampanga, a region that is known for its steep slopes and high susceptibility to monsoon rains and typhoons. As a preventative precaution against more soil erosion and infrastructure damage along a roadside embankment next to Rizal Street, the research focuses on developing an optimal reinforced concrete retaining wall. The study employs a mixed-methods approach that combines field surveys, qualitative interviews, and analysis using GIS, HEC-HMS, AutoCAD, and PLAXIS 2D. Different reinforced concrete retaining wall designs, particularly cantilever and counterfort designs, were assessed based on site compatibility, cost-effectiveness, and structural performance. Peak discharge and runoff were estimated using HEC-HMS, and slope stability under site-specific loading circumstances was ensured by acceptable lateral displacements validated by finite element modeling using PLAXIS 2D. These results confirm that the suggested construction is appropriate for reducing erosion and improving the impacted embankment's long-term safety and resilience. The cantilever wall design was suggested as the best option following comparative study, establishing a balance between structural soundness and practicality. This study serves as a model for comparable hazard-prone locations in semi-urban contexts and offers a workable, site-specific approach for slope stabilization and erosion management.